Economic poverty and inequality at regional level in Malta: Focus on the situation of children - Betti , Gianni; Caruana , Etienne; Gusman , Sarah; Neri , Laura (Economy of Regions, 2015)
This paper performs an economic poverty and inequality mapping of three children age categories in Malta; it consists in the first attempt based on income from the EU-SILC survey and Census data. From a policy-making point of view, the availability of such key economic indicators at locality level certainly provides a valuable tool in assessing the effectiveness of national strategies and in identifying areas that need to be targeted by new policies; in fact sample surveys alone cannot provide reliable information at such a fine level of detail, while national censuses are not designed to and cannot be extended to cover specific topics such as economic poverty and inequality. Thus, the merging of the two sources provides policy-makers with a new insight into the differences between localities. There are also benefits of a technical nature, particularly in terms of sampling strategies, that can be derived from this study. Through such an exercise it is possible to identify economic homogeneity and/or heterogeneity among households with children in different localities: this is useful when defining strata for sampling design for surveys aiming at studying other economic phenomena relating to children.